THE IMPACTS OF THE 2015 NATIONAL EXAMINATION POLICY IN INDONESIA ON ENGLISH LANGUAGE TEACHING - Wina Hartaty (Universitas Negeri Padang, 2017)
This case study aims to see how the 2015 policy on the national examination in Indonesia affects English language teaching in a public Islamic junior high school. This policy eliminates the passing grade requirements for students who take the national examination. The respondents were all three English teachers in the school. They took an online designed survey powered by Qualtrics to depict their teaching practices before and after the implementation of the policy. The survey included four themes, namely, the teaching objectives and learning mastery, the English teaching practices, the concerning factors in designing teaching activities, and the teaching satisfaction. The data were analysed using framework analysis. Some differences and similarities on the English language teaching are found in the teaching practices before and after the implementation of the new policy. The differences were found almost at all themes. One prominent finding is that the teachers felt teaching satisfaction due to the absence of target to achieve certain passing grade, which was previously implemented and caused the practice of teaching for test. This has shown that the new examination policy in Indonesia affects positively on the English language teaching in this school.